Analisis Pengaruh Tingkat Investasi dan Tingkat Pengangguran Terbuka Terhadap Indeks Pembangunan Manusia di Sumatra Utara Periode 2002-2021 - Mutia, Nazwa; Nasution, Rifka Aqiila; Zebua, Nobel Indah Clawdya; Maria, Santa (Universitas Labuhanbatu, 2023)
The Human Development Index (HDI) is an important indicator to measure success in efforts to build the quality of human life. The higher the number of Human Development Index, the better the population in the region. The research was conducted to see the long and short-term influence between the level of investment and the level of open unemployment on the Human Development Index. The data analysis technique used is ECM (Error Correction Model) analysis using the Eviews 9 analysis tool. The results prove that the independent variables of Investment and Open Unemployment Rate simultaneously together have a significant effect on the Human Development Index.